Emotional Divorce and Emotional Schemas in Couples with Emotional Divorce Experience: The Mediating Role of Emotional Intelligence - Entezarkheir, Neda; Alivandi Vafa, Marziyeh; Hosseini-Nasab, Seyyed Davoud (Applied Family Therapy Journal (AFTJ), 2022)
Aim: This study was conducted with the aim of emotional divorce and emotional schemas in couples with emotional divorce experience: the mediating role of emotional intelligence. Methods: The research method is cross-sectional correlation. The statistical population of this study consisted of all married women referring to counseling clinics in region 1 of Tehran with the field of couple therapy counseling in 1400, from which 220 people were selected by available sampling method. In this study, the tools of emotional divorce (Guttman, 1999), emotional schemas (Leahy, 2002) and emotional intelligence (Bar-On, 1980) were used, all of which had acceptable validity and reliability. SPSS-V22 and Amos-V22 software were used to analyze the data. Structural equation modeling was also used to answer the research hypotheses. Results: Findings showed that the model has a good fit. The results showed that emotional schemas did not have a direct effect on emotional divorce in couples with emotional divorce experience referred to Tehran Psychological Center. Conclusion: The results also showed that emotional schemas do not have an indirect effect on emotional divorce mediated by emotional intelligence in couples with emotional divorce experience referred to Tehran Psychological Center.